Mengeksplorasi Strategi yang Digunakan oleh Guru Bahasa Inggris dalam Pengajaran Menulis untuk Siswa Sekolah Menengah Pertama di Kota Bengkulu - Nur Annisa, Meti; Yunita, Wisma (JET (Journal of English Teaching), 2025)
Writing is a fundamental skill in English language learning that requires the application of effective instructional strategies. Various strategies have been implemented in writing classrooms, including writing strategies, summarization, collaborative writing, specific product goals, word processing, sentence combining, prewriting, inquiry activities, the process writing approach, the study of models, and writing for content learning. This study aimed at examining the writing strategies employed by English teachers in junior high schools. To achieve the objective, interviews were conducted with two experienced junior high school English teachers. The interview questions were developed based on the writing instruction framework proposed by Graham and Perin (2007). The data was analyzed descriptively using the content analysis technique. The findings reveal that teachers primarily utilize summarization, collaborative writing, sentence combining, inquiry activities, and the study of models in their writing instructions. Additionally, the teachers emphasized that these strategies are essential and effective in enhancing students' writing skills.